2016
DOI: 10.1002/humu.22957
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Analysis ofCCNOVariants in a Defined Population: Implications for Clinical Phenotype and Differential Diagnosis

Abstract: Reduced generation of multiple motile cilia (RGMC) is a novel chronic destructive airway disease within the group of mucociliary clearance disorders with only few cases reported. Mutations in two genes, CCNO and MCIDAS, have been identified as a cause of this disease, both leading to a greatly reduced number of cilia and causing impaired mucociliary clearance. This study was designed to identify the prevalence of CCNO mutations in Israel and further delineate the clinical characteristics of RGMC. We analyzed 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
83
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(90 citation statements)
references
References 21 publications
(65 reference statements)
3
83
2
2
Order By: Relevance
“…in DNAI1 [106] and DNAH5 [69]) and mutational hot spots (e.g. CCNO [107]) have been reported. The ranking of the effect of the mutations should follow international recommendations [108]: benign (class 1), likely benign (class 2), unknown significance (class 3), likely pathogenic (class 4), pathogenic (class 5).…”
Section: Resultsmentioning
confidence: 99%
“…in DNAI1 [106] and DNAH5 [69]) and mutational hot spots (e.g. CCNO [107]) have been reported. The ranking of the effect of the mutations should follow international recommendations [108]: benign (class 1), likely benign (class 2), unknown significance (class 3), likely pathogenic (class 4), pathogenic (class 5).…”
Section: Resultsmentioning
confidence: 99%
“…Downstream from the MCIDAS/E2F complex also lies CCNO ( Fig. 1) (Stubbs et al 2012;Ma et al 2014;Wallmeier et al 2014), a cyclin-like protein first shown to be involved in oocyte meiosis resumption and apoptosis (Roig et al 2009;Ma et al 2013), and then shown to be expressed in MCC progenitors in the Xenopus skin and in the mouse brain, airways, and oviducts (Stubbs et al 2012;Funk et al 2015;Amirav et al 2016). Although its partners and molecular function remain to be determined, CCNO mutations or depletion lead to defects comparable to the C-MYB phenotype: defects in BB amplification, docking, and ciliogenesis Funk et al 2015).…”
Section: Downstream Effectors Of the MCC Differentiation Programmentioning
confidence: 99%
“…Although its partners and molecular function remain to be determined, CCNO mutations or depletion lead to defects comparable to the C-MYB phenotype: defects in BB amplification, docking, and ciliogenesis Funk et al 2015). In humans, mutations in CCNO have been identified as a cause of RGMC and associated with hydrocephalus and female infertility Amirav et al 2016). Interestingly, human mcidas, ccno, and miR449 host gene cdc20b are physically colocalized in a genomic region of chromosome 5 and are syntenic with those of Xenopus and mouse (Marcet et al 2011;Stubbs et al 2012;Wallmeier et al 2014).…”
Section: Downstream Effectors Of the MCC Differentiation Programmentioning
confidence: 99%
“…Nasal nitric oxide values are low in patients with CCNO or MCIDAS mutations. 3537 High speed videomicroscopy analysis is normally unfeasible in these patients, as locating the few residual cilia per epithelial cell proves difficult, and reviewers often mistakenly conclude that the lack of cilia stems from a secondary process.…”
Section: Specific Forms Of Pcd With Normal Tem Ultrastructurementioning
confidence: 99%
“…11 However in one Israeli cohort with mucociliary clearance disorders, 11 out of 171 families (6.5%) had biallelic mutations in CCNO (n=10) or MICDAS (n=1) causing their disease. 37 An increased prevalence for PCD in the Irish Traveler population exists with the CCNO gene. 38 Mutations in CCNO and MCIDAS are detected on commercial PCD genetic panels.…”
Section: Specific Forms Of Pcd With Normal Tem Ultrastructurementioning
confidence: 99%